Conversion type nickel-copper sulfide negative electrode material, preparation and battery
The converted nickel -copper sulfide negative material is prepared through the constant current electrical deposition method, which solves the problem of the high expansion rate and low -level conductivity of sodium ion batteries, and achieves high -capacity and excellent cycle stability.
Patent Information
- Application Number
- CN202411493018.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing sodium ion battery negative electrode materials have poor circulation capacity and rate performance and poor stability due to high expansion rate and low intrinsic conductivity.
The negative material of the converted nickel -copper sulfide is prepared by the constant current electrical deposition method. The nickel, copper source, and sulfur source are mixed and dissolved in the electrolytes, the electrical deposition and annealing treatment to form a loose and porous three -dimensional flower accumulated by nanoparticles Form structure.
It improves the specific capacity and cycle stability of the battery, enhances the structural stability of the sodium-ion battery negative electrode, and shows excellent electrochemical performance.
Smart Images

Figure CN119352124A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and in particular to a conversion-type nickel-copper sulfide negative electrode material and preparation thereof, and a battery. Background Art
[0002] Energy issues are the shackles that restrict the development of human civilization and society, and the development of new energy technologies can not only promote technological progress, but also empower the economy. Lithium-ion batteries (LIBs) are widely used in our daily lives as a highly efficient energy conversion device. However, the shortage of lithium resources has led to soaring prices, which has limited its further development in the future. Sodium-ion batteries (SIBs) have similar charging and discharging mechanisms to lithium-ion batteries (LIBs), and sodium resources have been widely studied due to their low cost and wide distribution. In addition to cost advantages, SIBs also have unique advantages over LIBs, such as high safety and good high and low temperature performance. However, the radius of sodium ions is larger than that of lithium ions, making it difficult for their energy density and volume density to reach the level of lithium-ion batteries, which is mainly caused by electrode materials. Therefore, it is crucial to find a suitable SIBs electrode material.
[0003] Transition metal sulfides have the advantages of high theoretical capacity, multiple sodium ion storage mechanisms, strong thermodynamic stability, and low price, and are considered to be potential negative electrode materials for sodium ion batteries. The metal-S bond has a lower bond energy than the metal-O bond, which reduces the barrier in the sodiumation / de-sodiumation process. However, the high expansion rate of conversion transition metal sulfides makes them easy to pulverize during the charge and discharge process. In addition, the low intrinsic conductivity also limits the cycle capacity and rate performance. Summary of the invention
[0004] 1. Problem to be solved
[0005] In view of the problems of high expansion rate and poor stability of existing negative electrode materials for sodium ion batteries, the present invention provides a conversion-type nickel-copper sulfide negative electrode material and a preparation method thereof.
[0006] 2. Technical solution
[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0008] In a first aspect, the present invention provides a method for preparing a conversion-type nickel-copper sulfide negative electrode material, comprising the following steps:
[0009] S1. Preparing an electrolyte: dissolving a nickel source, a copper source, a sulfur source and ammonium chloride in a solvent, stirring and dissolving to obtain an electrolyte;
[0010] S2. Electrodeposition: using the electrolyte in step S1, electrodeposition is performed in a three-electrode system, and after the electrodeposition is completed, the electrodeposition product is cleaned and dried to obtain;
[0011] S3. Annealing treatment: annealing the electrodeposited product in step S2 to obtain a conversion-type nickel-copper sulfide negative electrode material.
[0012] The advantages of adopting the above technical solution are: first, the present invention combines nickel sulfide with high capacity and copper sulfide with good conductivity, taking into account both capacity and conductivity, and due to the synergistic effect between multiple metals, the specific capacity of the battery is improved; the main purpose of introducing copper elements is to introduce more sodium storage sites, improve the morphology of the multi-metal sulfide, i.e., the conversion-type nickel-copper sulfide negative electrode material, reduce the volume expansion during the cycle, and improve the cycle stability;
[0013] Secondly, the constant current electrodeposition method is used to synthesize the conversion type nickel copper sulfide negative electrode material. Its preparation process is simple and easy to operate, which greatly reduces the preparation cost of the electrode material, and the preparation process is green and environmentally friendly.
[0014] Finally, after annealing treatment, a conversion-type nickel-copper sulfide negative electrode material was obtained, which was used as the negative electrode of a sodium ion battery after sheeting. This enhanced the structural stability of the negative electrode during the sodium ion battery cycle and showed excellent electrochemical performance.
[0015] It should be noted that the electrodeposition product on the working electrode in the three-electrode system in step S2 can be removed and annealed to obtain a conversion-type nickel-copper sulfide negative electrode material; or the working electrode and the electrodeposition product in step S2 can be annealed at the same time, and then the conversion-type nickel-copper sulfide negative electrode material can be removed.
[0016] Furthermore, in step S2, the electrodeposition conditions are: constant current density: 0.1-5 A·cm -2 ; Electrodeposition time: 20~150s.
[0017] The advantages of the above technical solution are: if the current density is too low, the coating, i.e. the electrodeposition product, will be dense, and if the current density is too high, the coating will be too loose. -2 It is a reasonable current density; too long electrodeposition time will lead to too thick a coating, and too short a coating will lead to too thin a coating. 20 to 150 seconds is a reasonable electrodeposition time.
[0018] Furthermore, in step S2, the cleaning specifically includes: cleaning with deionized water.
[0019] Furthermore, in step S2, the drying conditions include: drying temperature: 50-100°C; drying time: 1-5h.
[0020] For example, drying can be performed using a vacuum drying oven.
[0021] Further, in step S2, the three-electrode system includes a working electrode, a counter electrode and a reference electrode;
[0022] Wherein, the working electrode is a current collector,
[0023] The working electrode includes at least one of copper foil, aluminum foil, nickel foam, and copper foam.
[0024] Furthermore, the counter electrode includes at least one of a Pt sheet and a carbon rod.
[0025] Furthermore, the reference electrode includes at least one of a saturated calomel electrode and a silver / silver chloride electrode.
[0026] Furthermore, in step S1, the conditions for preparing the electrolyte include: preparation temperature: 20-30°C, preferably room temperature 25°C.
[0027] The advantages of adopting the above technical solution are: the preparation method can be carried out at room temperature, there is no need to control the temperature, the conditions are mild, and the operation is simple.
[0028] Furthermore, in step S1, the nickel source includes at least one of nickel chloride, nickel acetate, nickel sulfate, and nickel nitrate.
[0029] Furthermore, in step S1, the copper source includes at least one of copper chloride, copper acetate, copper sulfate and copper nitrate.
[0030] Furthermore, in step S1, the sulfur source includes at least one of sodium sulfide nonahydrate, sodium thiosulfate, thioacetamide, and thiourea.
[0031] Furthermore, in step S1, the concentrations of the nickel source, the copper source and the sulfur source in the electrolyte are 0.1-0.3 mol / L, 0.01-0.2 mol / L and 0.1-0.6 mol / L respectively.
[0032] The reason for adopting the above technical solution is that: the nickel source, copper source and sulfur source are controlled within the above range, and the prepared nickel-copper sulfide is formed by the accumulation of nanoparticles, presenting a loose and porous three-dimensional flower-like structure, and the particles are evenly distributed, which is beneficial to increase the contact area between the negative electrode material and the electrolyte, provide more exposed active sites, shorten the sodium ion diffusion path, and improve the transmission efficiency of ions or electrons.
[0033] Furthermore, in step S1, the concentration of ammonium chloride in the electrolyte is 0.1-0.3 mol / L.
[0034] Furthermore, in step S1, the solvent includes at least one of deionized water, distilled water, reverse osmosis water, ultrapure water and double distilled water.
[0035] Furthermore, in step S1, the stirring and dissolving can be performed by magnetic stirring.
[0036] Furthermore, the step S1 is specifically as follows:
[0037] First, add ammonium chloride to the solvent and stir until it is completely dissolved;
[0038] Then add nickel source and copper source, and stir until completely dissolved;
[0039] Then add the sulfur source and stir until it is completely dissolved to obtain an electrolyte.
[0040] Furthermore, in step S3, the annealing conditions include: annealing temperature: 300-600° C.; annealing time: 2-5 h.
[0041] For example, the annealing process can be carried out in an annealing tube furnace.
[0042] The reason for adopting the above technical solution is that controlling the annealing temperature and time within the above range is beneficial to improving the conductivity and thermal stability of the material.
[0043] Furthermore, in step S3, the annealing conditions further include: the annealing is performed in an inert gas atmosphere or under vacuum conditions.
[0044] The reason for adopting the above technical solution is that the inert gas atmosphere can protect the deposited product from being affected by oxidation or other chemical reactions during the annealing process; in addition, the vacuum environment can also prevent the electrodeposited product from reacting with any gas molecules at high temperature.
[0045] Furthermore, the inert gas includes at least one of nitrogen, argon and helium.
[0046] Furthermore, the inert gas is nitrogen.
[0047] The reason for adopting the above technical solution is that nitrogen is the gas with the highest content in the atmosphere, so it is relatively easy to obtain and has low cost, and its chemical stability is good.
[0048] In a second aspect, the present invention also provides a conversion type nickel copper sulfide negative electrode material prepared by the above preparation method;
[0049] The conversion-type nickel-copper sulfide negative electrode material is a three-dimensional flower-like structure formed by the accumulation of nanoparticles.
[0050] Furthermore, the conversion-type nickel-copper sulfide negative electrode material is a loose, porous, three-dimensional flower-like structure formed by the accumulation of nanoparticles; the nanoparticles are evenly distributed, and the even distribution means that within a certain spatial range, the arrangement of the particles presents a relatively balanced and consistent state, that is, there is no significant local deviation or aggregation phenomenon in the spacing, density or number distribution between the particles.
[0051] Furthermore, the particle size of the nanoparticles is 50 to 500 nm.
[0052] In a third aspect, the present invention provides a sodium ion battery, comprising a negative electrode, wherein the negative electrode comprises the conversion-type nickel-copper sulfide negative electrode material prepared by the above preparation method or the above conversion-type nickel-copper sulfide negative electrode material.
[0053] The reason for adopting the above technical solution is that the negative electrode of the sodium ion battery includes the above conversion-type nickel-copper sulfide negative electrode material, which has higher capacity and longer service life.
[0054] 3. Beneficial effects
[0055] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides a method for preparing a conversion-type nickel-copper sulfide negative electrode material by electrodeposition, and the obtained negative electrode material not only has a higher capacity, but also has the advantages of better kinetic performance, higher stability, etc., which meets the requirements of sodium ion battery negative electrode design.
[0056] More specifically, it has the following beneficial effects:
[0057] (1) The preparation method of the conversion type nickel copper sulfide negative electrode material provided by the present invention adopts a simple constant current electrodeposition method to form the conversion type nickel copper sulfide negative electrode material on the current collector substrate. This method has the advantages of simple synthesis and mild conditions, meets the requirements of green development, and is conducive to industrial application and promotion.
[0058] (2) The conversion-type nickel-copper sulfide negative electrode material provided by the present invention is formed by the accumulation of nanoparticles and presents a loose and porous three-dimensional flower-like structure with uniformly distributed particles. Such a structure increases the contact area between the negative electrode material and the electrolyte, provides more exposed active sites, shortens the sodium ion diffusion path, and improves the transmission efficiency of ions or electrons.
[0059] (3) The conversion-type nickel-copper sulfide negative electrode material provided by the present invention effectively mitigates the serious structural damage of the electrode material caused by volume change during the sodium ion insertion / extraction process, overcomes the shortcomings of high expansion rate and easy pulverization of the conversion-type transition metal sulfide, and improves the cycle stability of the electrode material.
[0060] (4) The sodium ion battery negative electrode material of the present invention exhibits high capacity and excellent cycle stability, and is a potential application material for high-capacity and long-life sodium ion batteries, and has potential large-scale market application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is a scanning electron microscope image of the conversion type nickel-copper sulfide negative electrode material prepared in Example 1 of the present invention;
[0062] Figure 2 This is a cycle performance diagram of the conversion-type nickel-copper sulfide negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0063] The present disclosure may be more easily understood by reference to the following description in conjunction with examples, all of which constitute a part of the present disclosure. It should be understood that the present disclosure is not limited to the specific products, methods, conditions or parameters described and / or illustrated herein. Further, the terms used herein are only used for the purpose of describing specific embodiments by way of example and are not intended to be limiting unless otherwise indicated.
[0064] It should also be understood that, for the sake of clarity, certain features of the present disclosure may be described herein in the context of separate embodiments, but may also be provided in combination with each other in a single embodiment. That is, unless clearly incompatible or specifically not included, each separate embodiment is considered to be combinable with any other embodiment, and the combination is considered to represent another different embodiment. Conversely, for the sake of simplicity, the various features of the present disclosure described in the context of a single embodiment may also be provided individually or in any sub-combination. Finally, although a particular embodiment may be described as part of a series of steps or part of a more general structure, each step or substructure itself may also be considered to be an independent embodiment.
[0065] In the present disclosure, the singular forms of the articles "a," "an," and "the" also include the corresponding plural references, and a reference to a specific value includes at least that specific value unless the context clearly indicates otherwise. Thus, for example, a reference to "a substance" is a reference to at least one of that substance and equivalents thereof.
[0066] In general, the use of the term "about" indicates an approximate value that can vary depending on the desired properties obtained by the disclosed subject matter, and will be interpreted in a context-dependent manner based on function. Therefore, one of ordinary skill in the art will be able to interpret a certain degree of difference on a case-by-case basis. In some cases, the number of significant figures used when expressing a particular value can be a representative technique for determining the difference allowed by the term "about". In other cases, a gradient in a range of values can be used to determine the range of differences allowed by the term "about". Further, all ranges in this disclosure are inclusive and combinable, and reference to a value in a range includes each value within that range.
[0067] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the terms used herein and / or include any and all combinations of one or more of the associated listed items.
[0068] In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be purchased commercially.
[0069] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The essential characteristics and remarkable effects of the present invention can be reflected from the following examples, and the described embodiments are part of the embodiments of the present invention, rather than all the embodiments, and therefore, they do not limit the present invention in any way, and those skilled in the art make some non-essential improvements and adjustments based on the content of the present invention, which all belong to the protection scope of the present invention.
[0070] The present invention is further described below in conjunction with specific embodiments.
[0071] Example 1
[0072] This embodiment provides a method for preparing a conversion-type nickel-copper sulfide negative electrode material, specifically, comprising the following steps:
[0073] (1) Dissolve 0.025 mol NH4Cl in 100 mL deionized water and stir magnetically until completely dissolved.
[0074] (2) Add 0.02 mol NiCl2 and 0.005 mol CuCl2 to the solution obtained in step (1), and stir until completely dissolved to obtain a light green solution.
[0075] (3) Add 0.02 mol of thiourea to the solution obtained in step (2), and stir until it is completely dissolved to obtain the electrolyte for the deposition process.
[0076] In this embodiment, steps (1) to (3) are carried out at room temperature, and the stirring speed is 600 rpm / min.
[0077] (4) In the three-electrode system, copper foil was used as the working electrode, Pt sheet was used as the counter electrode, and Ag / AgCl electrode was used as the reference electrode. -2 The samples were deposited at a constant current density of 50 s. After the deposition was completed, they were carefully rinsed with deionized water and dried in a vacuum drying oven at a temperature of 60 °C for 4 h.
[0078] (5) The product was annealed at 500° C. for 3 h in a tubular furnace under the protection of an inert gas (nitrogen) atmosphere to obtain a conversion-type nickel-copper sulfide negative electrode material.
[0079] (6) The nickel-copper sulfide negative electrode material was scraped off the current collector, and the nickel-copper sulfide negative electrode material powder was fully ground with Super P (TIMCAL SUPER P LI) and PVDF (Arkema HSV-900) in a mortar at a mass ratio of 8:1:1. The slurry was prepared using NMP and coated on a copper foil (thickness of 8 μm) with a loading of 6 mg / cm 2 .
[0080] (7) The electrochemical properties of the material were tested using a commercially available sodium sheet (15.6×0.4 mm, Jiaxing Changgao New Material Technology Co., Ltd.) as the counter electrode, glass fiber (GF / D) as the separator, and 1 M NaPF6 dissolved in a solvent (EC:DMC=1:1 (volume ratio)) as the electrolyte.
[0081] Figure 1 This is a scanning electron microscope image of the conversion type nickel copper sulfide negative electrode material synthesized in this embodiment. The conversion type nickel copper sulfide has distinct morphological characteristics and is a loose porous three-dimensional flower-like structure formed by the accumulation of uniformly distributed nanoparticles. The particle diameter is about 50 to 500 nm.
[0082] Figure 2 This is a rate performance diagram of the conversion-type nickel-copper sulfide negative electrode material synthesized in this embodiment, wherein the discharge specific capacity is 415.53 mAh / g at a current density of 0.1 A / g, and the discharge specific capacity is 353.2 mAh / g at a current density of 5 A / g.
[0083] Example 2
[0084] This embodiment provides a method for preparing a conversion-type nickel-copper sulfide negative electrode material, which is basically the same as that of Embodiment 1, except that:
[0085] In step (2), the amount of CuCl2 added is 0.002 mol.
[0086] The negative electrode material of this embodiment has a discharge specific capacity of 388.64 mAh / g at a current density of 0.1 A / g.
[0087] Example 3
[0088] This embodiment provides a method for preparing a conversion-type nickel-copper sulfide negative electrode material, which is basically the same as that of Embodiment 1, except that:
[0089] In step (2), the amount of CuCl2 added is 0.01 mol.
[0090] The negative electrode material of this embodiment has a discharge specific capacity of 390.66 mAh / g at a current density of 0.1 A / g.
[0091] Example 4
[0092] This embodiment provides a method for preparing a conversion-type nickel-copper sulfide negative electrode material, which is basically the same as that of Embodiment 1, except that:
[0093] In step (2), the amount of CuCl2 added is 0.015 mol.
[0094] The negative electrode material of this embodiment has a discharge specific capacity of 368.53 mAh / g at a current density of 0.1 A / g.
[0095] Comparative Example 1
[0096] This comparative example provides a method for preparing a conversion-type nickel-copper sulfide negative electrode material, which is basically the same as Example 1, except that:
[0097] In step (2), no CuCl2 is added, and only 0.02 mol NiCl2 is added.
[0098] The negative electrode material of this comparative example has a discharge specific capacity of 303.99 mAh / g at a current density of 0.1 A / g.
[0099] Since no copper element is added in this comparative example, fewer sodium storage sites are exposed, the ion diffusion distance is longer, and the sodiumization / de-sodiumization barrier of the monometallic sulfide is higher, so its capacity is lower.
[0100] Comparative Example 2
[0101] This comparative example provides a method for preparing a conversion-type nickel-copper sulfide negative electrode material, which is basically the same as Example 1, except that:
[0102] In step (2), no NiCl2 is added, and only 0.005 mol CuCl2 is added.
[0103] The negative electrode material of this comparative example has a discharge specific capacity of 118.92 mAh / g at a current density of 0.1 A / g.
[0104] Since no nickel element is added to this comparative example, its intrinsic sodium storage capacity is relatively low, so its capacity is relatively low.
Claims
1. A method for preparing a conversion-type nickel-copper sulfide negative electrode material, characterized in that: The following steps are involved: S1. Preparing an electrolyte: dissolving a nickel source, a copper source, a sulfur source and ammonium chloride in a solvent, stirring and dissolving to obtain an electrolyte; S2. Electrodeposition: using the electrolyte in step S1, electrodeposition is performed in a three-electrode system, and after the electrodeposition is completed, the electrodeposition product is cleaned and dried to obtain; S3. Annealing treatment: annealing the electrodeposited product in step S2 to obtain a conversion-type nickel-copper sulfide negative electrode material.
2. The method for preparing the conversion type nickel copper sulfide negative electrode material according to claim 1, characterized in that: In step S2, the conditions for the electrodeposition are: Constant current density: 0.1~5A·cm -2 ; Electrodeposition time: 20 to 150 seconds.
3. The method for preparing a conversion-type nickel-copper sulfide negative electrode material according to any one of claims 1 or 2, characterized in that: In step S1, the concentrations of the nickel source, copper source and sulfur source in the electrolyte are 0.1-0.3 mol / L, 0.01-0.2 mol / L and 0.1-0.6 mol / L respectively.
4. The method for preparing the conversion type nickel copper sulfide negative electrode material according to claim 3, characterized in that: In step S1, the nickel source includes at least one of nickel chloride, nickel acetate, nickel sulfate, and nickel nitrate; The copper source includes at least one of copper chloride, copper acetate, copper sulfate and copper nitrate; The sulfur source includes at least one of sodium sulfide nonahydrate, sodium thiosulfate, thioacetamide, and thiourea.
5. The method for preparing the conversion type nickel copper sulfide negative electrode material according to claim 3, characterized in that: In step S2, the three-electrode system includes a working electrode, a counter electrode, and a reference electrode; Wherein, the working electrode is a current collector; The working electrode comprises at least one of copper foil, aluminum foil, nickel foam and copper foam; The counter electrode comprises at least one of a Pt sheet and a carbon rod; The reference electrode includes at least one of a saturated calomel electrode and a silver / silver chloride electrode.
6. The method for preparing the conversion type nickel copper sulfide negative electrode material according to claim 5, characterized in that: In step S3, the annealing conditions include: Annealing temperature: 300~600℃; Annealing time: 2 to 5 hours.
7. The method for preparing the conversion type nickel-copper sulfide negative electrode material according to claim 6, characterized in that: In step S3, the annealing conditions further include: the annealing is performed in an inert gas atmosphere or under vacuum conditions.
8. A conversion type nickel copper sulfide negative electrode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The conversion-type nickel-copper sulfide negative electrode material is a three-dimensional flower-like structure formed by the accumulation of nanoparticles.
9. The conversion type nickel-copper sulfide negative electrode material according to claim 8, characterized in that: The particle size of the nanoparticles is 50 to 500 nm.
10. A sodium ion battery, comprising a negative electrode, characterized in that the negative electrode comprises a conversion type nickel copper sulfide negative electrode material prepared by the preparation method according to any one of claims 1 to 7 or a conversion type nickel copper sulfide negative electrode material according to any one of claims 8 to 9.
Citation Information
Patent Citations
High-capacity flexible anode material for lithium-ion batteries and preparation method thereof
CN107452939A
Method for preparing nickel-iron sulfide nano-composite electrode through one-step electrodeposition
CN113793760A
Transition metal sulfide modified electrode and preparation method and application thereof
CN114614030A
Synthesis method of flower-shaped hierarchical nanostructure bimetallic sulfide electrode material
CN115180660A
Binary transition metal sulfide composite material, preparation method and application thereof
CN115377375A